Using Translanguaging Pedagogy to Teach Naming and Action Words An Exploration into an Indian Primary Level English as a Second Language (ESL) Classroom - Mukhopadhyay, Lina (JOURNAL OF INDIAN EDUCATION, 2020)
An ESL class session from an Indian primary level government school is analysed in this paper as one instance of use of teacher-led translanguaging for pedagogic purposes. This classroom observation was done post a training programme, where teachers from primary grades in Hyderabad were given structured inputs to use various multilingual strategies to teach language and content. The analysis shows that translanguaging is used to clarify concepts, instruct students and help them participate in classroom activities. Teacher reflection adds to our understanding of the usefulness of translanguaging to employ students’ L1 more systematically, to help them learn about a set of naming and action words in English by drawing equivalent lexical comparisons between Telugu (L1), Hindi (L1) and English (L3). Instances of use of translanguaging or fluid ways of communicating using multiple languages in class helps in validating the practice todevelop linguistic skills in students who do not get exposure to English at home.